LEAN SIX SIGMA AND ELECTRONIC RECIPES IN EFFORTS TO IMPROVE PATIENT SAFETY IN THE INSTALLATION OF EMERGENCY SANGLAH DENPASAR HOSPITAL - Nariyantha, I Kadek; Astawa, I Nengah Dasi (FEB Universitas Sam Ratulangi Manado, 2020)
ABSTRACT: Introduction: Patient safety is a trending topic in various hospitals. Patient safety involves preventing mistakes and eliminating various dangers due to errors and can occur at any time during the health care process, especially in the treatment of patients. Research Objectives: This study aims to determine how the implementation of Lean Six Sigma in electronic prescription services by calculating the incidence of potentially medication errors analyzed by Six Sigma is used to determine improvements in the quality of prescription services. Research Methods: The method used in this study is a mix method. The first step was to observe the implementation of recipes with a sample size of 100 recipes then the second stage conducted in-depth interviews with 20 respondents. Research Result: defect of prescription service by 2.25% with a sigma value of 3.50 means that electronic prescription service is good enough but needs improvement. Conclusion: Six sigma can be used as an evaluation in an effort to improve the quality of electronic prescription services, electronic prescriptions can reduce the incidence of medication errors as an effort to improve patient safety in the Emergency Department of Sanglah Hospital. The results of interviews with informants agreed that electronic prescriptions could improve patient safety.Â Keywords: Â lean six sigma, electronic prescriptions, medication errors, patient safety.